Hemodynamics following Prophylactic Phenylephrine Infusion in patients undergoing Cesarean Section under Spinal Anesthesia - Gauchan, Sabin; Thapa, Chitra; Acharya, Sulav; Khanal, Anupa (Journal of Institute of Medicine Nepal, 2024)
Introduction Phenylephrine is considered the vasopressor of choice in hypotension associated with obstetric spinal anesthesia. But the dose and mode of administration that is effective yet safe in mother as well as fetus remains controversial. We studied the hemodynamics of parturients who received prophylactic infusion of phenylephrine 50µg/min following spinal anesthesia. Methods Patients posted for elective cesarean section received a prophylactic phenylephrine infusion of 50µg/min immediately after spinal anesthesia for 30 minutes. Parturients were also co-loaded with lactated Ringer’s solution 1 litre. Blood pressure and heart rate was monitored at an interval of 3min initially and after the delivery of baby interval was increased to 5min. Episodes of hypotension, reactive hypertension and bradycardia in mother were recorded. Neonatal APGAR score at 1 and 5min was also recorded. Results One hundred and forty parturients were included in the study. Twenty patients (14.28%) developed hypotension. Out of 20 patients who developed hypotension, 3 patients (15%) had a single episode, 11 patients (55%) had 2 episodes and 6 patients (30%) had 3 episodes of hypotension. Three patients (2.14%) had reactive hypertension. None of the patients had bradycardia. There was no episode of hypotension induced nausea vomiting. Mean APGAR score at 1min and 5min was 8 and 9 respectively. Conclusion The prevalence of hypotension with prophylactic phenylephrine infusion was low. We found minimal episodes of reactive hypertension, no episodes of bradycardia and no adverse effect on fetus. It can be regarded a safe means to minimize hypotension in obstetric spinal anesthesia.